NASP implication in the androgen receptor associated with castration resistance in prostate cancer - Yun Feng; Jin Sun; Xuan Kang; Yining Wang; Kai Liu; Wenfei Wang; Chen Wang; Yabin Li; Qian Zhao; Kaile Li; Fang-Lin Sun; Jianfeng Chang (Cell Communication and Signaling)
Abstract Uncovering the mechanisms underlying tumor malignancy is extremely important for cancer treatment and management. In this study, using a pairwise cell model, LNCaP and its castration-resistant derivative C42B, we analyze the function of enhanced NASP protein in castration resistance. The data show that the expression of androgen receptor-targeted genes was obviously affected by NASP knockdown in C42B cells, and nearly 20% of the differential genes were AR dependent. ATAC-seq analysis revealed that NASP knockdown in C42B cells comprehensively increased chromatin accessibility, and disorders at AR occupancy regions were more prominent. Castration-induced genes, especially androgen-independent AR target genes, were enriched in the downregulated gene group. Further analysis of high-order chromatin interactions revealed that NASP knockdown in C42B led to frequent changes in multiple layers, including the compartment A/B transition, TAD boundary distance and chromatin loop, and AR-binding regions especially underwent more extensive reconstruction. Finally, we found that the recovery of the histone H3 pool in C42B can actually recall H3 back to the previous regions with both H3 and AR loss induced by NASP knockdown, but AR rebinding to the corresponding sites is obviously inhibited and lagging. These data indicate that NASP plays a fundamental role in guarding proper and fine mechanisms of AR in prostate cancer promotion and malignancy.